(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Ovarian carcinosarcoma (Malignant Mixed Mesodermal Tumour) is rare malignant tumour with a poor prognosis. We here present a case of ovarian carcinosarcoma in a 72-yearswoman suffering from intermittent lower abdominal pain for 5 months with previous history of Total Abdominal Hysterectomy (TAH) with Unilateral Salpingo-Oophorectomy (USO) due to leiomyoma 27 years back. Explanatory laparotomy and right salpingo-oophorectomy with complete surgical staging was done at Dhaka Community Medical College Hospital. Histopathology revealed both sarcomatous and carcinomatous component. Surprisingly the patient had no metastatic foci and consulted with a medical Oncologist, who didn’t recommend any chemotherapy and was cancer free during last one and half years follow up. Bangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 124-126